The sorcerer's apprentice [videorecording (DVD)] - Turteltaub, Jon; Baruchel, Jay, 1982-; Bellucci, Monica, 1968-; Cage, Nicolas, 1965-; Palmer, Teresa, 1986-; Molina, Alfred, 1953- (Disney : Distributed by Buena Vista Home Entertainment, 2010)
Balthazar Blake is a modern-day sorcerer with his hands full defending Manhattan against dark forces. When a seemingly average kid shows hidden potential, Balthazar takes his reluctant recruit on a crash course in the art and science of magic to become the ultimate sorcerer's apprentice.